Corrigenda to Gil-Santana, H.R. 2018. A new species of Phasmatocoris from French Guiana, with short taxonomic notes on two described species and an updated key (Hemiptera: Heteroptera: Reduviidae: Emesinae). Zootaxa 4413 (3): 491–506 - Gil-Santana, Hélcio R. (Zootaxa, 2018)
An intraspecific variation of the male genitalia of Phasmatocoris papei Gil-Santana, 2018 (Hemiptera: Heteroptera: Reduviidae: Emesinae: Emesini), i.e., the absence (holotype) / presence (paratype) of the sclerotization of approximately basal two thirds of the ventral wall of phallosoma, reported by Gil-Santana (2018), was found to be incorrect. A subsequent reexamination of the specimens revealed that the misjudgement was based on a breakage of this structure in the phallus of the holotype. In fact, the ventral wall of phallosoma was completely sclerotized at its basal two-thirds in both specimens and should be considered as a species level character of Ph. papei.